Interrogating the Transient Selectivity of Bacterial Chemotaxis-Driven Affinity and Accumulation of Carbonaceous Substances via Raman Microspectroscopy - Li, Hanbing; Martin, Francis L.; Jones, Kevin C.; Zhang, Dayi (Frontiers in Microbiology, 2019)
Carbonaceous substances are fundamental organic nutrients for microbial metabolism and catabolism in natural habitats. Microbial abilities to sense, accumulate and utilize organic carbonaceous substances in the complex nutrient environment are important for their growth and ecological functions. Bacterial chemotaxis is an effective mechanism for microbial utilization of carbonaceous substances under nutrient depletion conditions. Although bacterial accumulation and utilization to individual carbonaceous substance in long-term cultivation has been well studied, their selective affinity of mixed carbonaceous substances remains to be investigated, primarily because of technical limitations of conventional methods. Herein, we applied Raman microspectroscopy to identify chemotaxis-driven affinity and accumulation of four organic carbonaceous substances (glucose, succinate, acetate and salicylate) by three bacterial strains (Acinetobacter baylyi, Pseudomonas fluorescence and Escherichia coli). A. baylyi exhibited strong binding affinity towards glucose and succinate, whereas P. fluorescence and E. coli were preferentially responsive to glucose and acetate. For the first time, bacterial transient selectivity of carbonaceous substances was studied via interrogating Raman spectral alterations. Post-exposure to carbonaceous-substance mixtures, the three bacterial strains showed distinct selective behaviors. Stronger selective affinity enhanced the chemotaxis-related signal transduction in A. baylyi cells, whereas the carbonaceous substance signal transduction in E. coli was decreased by higher selective affinity. In P. fluorescence, there was no specific effect of selective affinity on signal transduction. Our study suggests that Raman microspectroscopy can successfully investigate and distinguish different scenarios of bacterial competitive and transient unitization of organic carbonaceous substances.